Imaginary Projections: Spinoza between Borges, Perón, and Freud - de Gainza, Mariana Cecilia (2021)
Academics and researchers, but also musicians, poets, writers, politicians, activists and people of a large variety of inscriptions and origins have expressed a strange love for Spinoza. Borges and Perón, a couple of famous enemies, are part of this universal current, that connect heterogenous historical modes of imagination. If a certain kind of unconscious takes part of the actualization of Spinoza over times, we have to think also in Freud, who was not alien to this Spinozian affinity, and in the way immanence has to do with a passion for knowledge.